Determination of the recombination rate coefficients for Na-like SiIV forming Mg-like SiIII - ALTUN, ZİKRİ (EDP SCIENCES S A, 2006)
Aims. Absolute, total recombination rate coefficients for Si IV were determined using the CRYING heavy-ion storage ring. Calculated rate coefficients were used to estimate recombination into states that could not be detected in the experiment because of field ionization. Total, as well as separate, radiative and dielectronic plasma recombination rate coefficients were determined. Methods. Stored ions were merged with an expanded electron beam in the electron cooler section of the storage ring. Recombined ions were separated from the stored ion beam in the first dipole magnet after the electron cooler and were detected with unity efficiency. The absolute radiative and dielectronic recombination rate coefficients were obtained over a center-of-mass energy range of 0-20 eV, covering. Delta n = 0 core excitations up to the 3s -> 3d series limit. The results of an intermediate coupling AUTOSTRUCTURE calculation were compared with the experiment. The theoretical results were also used to estimate the contribution to dielectronic recombination by high Rydberg states, which were not detected because of field ionization. The spectra were convoluted with Maxwell-Boltzmann energy distributions in the 10(3)-10(6) K temperature range. Results. The resulting plasma recombination rate coefficients are presented and compared with theoretical results frequently used for plasma modeling. In the 10(3)-10(4) K range, a significant underestimation of the calculated dielectronic recombination plasma rate coefficients was observed. Above 3 x 104 K, the agreement between our dielectronic recombination plasma rate coefficients and two of the previously published rate coefficients is better than 20%. Conclusions. The observed differences between the experimental and calculated recombination rate coefficients at low temperatures reflect the need for benchmarking experiments. Our experimentally-derived rate coefficients can guide the development of better theoretical models and lead to more accurately-calculated rate coefficients.
Keywords: atomic data; atomic processes; plasmas; FINITE-DENSITY PLASMAS; DIELECTRONIC RECOMBINATION; RADIATIVE RECOMBINATION; IONIZATION EQUILIBRIUM; IONS; ARGON